Hematopoietic Stem Cell Transplantation for Pediatric Acute Lymphoblastic Leukemia - SBTMO/SOPOBE 2020 Consensus Guidelines: SBTMO/SOPOBE Guidelines: Pediatric ALL - Daudt, Liane Esteves; Macedo, Antonio Vaz de; Guimaraes, Renata Fittipaldi; Fernandes Junior, Virginio Climaco de Araujo; Colturato, Maura R V Ikoma; Castro Junior, Claudio Galvão de; Domingues, Luciana dos Santos; Seber, Adriana (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a potentially curative approach to children and adolescents with high-risk acute lymphoblastic leukemia (ALL) at diagnosis or relapsed disease. Nonetheless, despite the graft versus leukemia (GVL) effect, treatment-related morbidity and mortality remains a major challenge. Moreover, the significant heterogeneity of the available data on the selection of patients, type of conditioning regimen, and type of donor hampers any definitive conclusions in the pediatric population. In 2020, the Brazilian Group for Pediatric Bone Marrow Transplantation of the Brazilian Society of Bone Marrow Transplantation and Cellular Therapy (SBTMO) and the Brazilian Society for Pediatric Oncology (SOBOPE) convened a task force to provide general guidance on HSCT for childhood ALL to providing evidence-based guidance for the appropriate management of this disease.